Fundamentals of nursing - DeLaune, Sue C.; Ladner, Patricia K.; McTier, Lauren; Tollefson, Joanne (Southbank, Victoria Australia : Cengage Learning Australia, 2024)
"Fundamentals of Nursing, Australian and New Zealand 3rd edition, covers nursing concepts, skills and standards of practice for introductory nursing students (Bachelor of Nursing). You will learn the core themes of nursing, including nurse, person, health and environment, as well as how to apply critical thinking skills for culturally diverse populations in a variety of clinical environments. Based on the concepts of research and evidence-based practice, this text not only informs, but challenges you to assess your own nursing practice and apply the concepts you learn in class to real-life, clinical settings. Complemented by the best-selling Clinical Psychomotor Skills: Assessment tools for Nursing by Joanne Tollefson and Elspeth Hillman. A value pack of these two texts is available for you to purchase"-- Worldcat.
Unit 1. Nursing perspectives: past, present and future -- Evolution of nursing education and theory -- Research and evidence-based practice -- Health care delivery -- Unit 2. Nursing process: the standard of care -- Critical thinking, decision-making and the nursing process -- Clinical assessment -- Problem identification -- Planning -- Implementation -- Evaluation -- Unit 3. Professional accountability -- Leadership and delegation -- Legal and ethical responsibilities -- Documentation and informatics -- Unit 4. Promoting health -- Nursing, healing and caring -- Communication -- Health and wellness promotion -- Family and community health -- The life cycle -- Paediatric care -- The older adult -- Palliative care -- Cultural diversity -- Aboriginal and Torres Strait Islander People's health -- Rural and remote health -- Health care education -- Unit 5. Responding to basic psychosocial needs -- Self-concept -- Stress, anxiety, adaption and change -- Spirituality -- Loss and grief -- Mental health -- Unit 6. Responding to basic psychological needs -- Vital signs -- Physical assessment -- Safety, infection control and hygiene -- Medication administration -- Traditional and complementary therapies -- Oxygenation -- Fluids and electrolytes -- Nutrition -- Pain management, comfort and sleep -- Mobility -- Skin integrity and wound healing -- Sensation, perception and cognition -- Elimination -- Perioperative nursing care.
3rd Australia & New Zealand edition.
Includes bibliographical references and index.
Keywords: Nurse and patient; Nursing -- Practice; Nursing -- Textbooks; Nursing Process; Nursing Care